Implementasi Mata Kuliah Pengemasan dan Penyimpanan Pangan dalam Kegiatan Pengabdian Masyarakat : Penerapan Labeling pada Kemasan Produk Pangan - Almaniar, Siska; Pamungkas, Ilham Wahyu; Agustin, Venny; Hijri, Nurul; Dwi Cahyo, Ali Mas'ud (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
Labels on food packaging play a crucial role in providing accurate information to consumers regarding product contents, safety, and usage instructions. Clear and regulated labeling helps consumers make informed decisions and avoid health risks due to improper consumption. A labeling awareness program was conducted using the Project Based Learning (PjBL) approach within the Food Packaging and Storage course at Politeknik Negeri Sriwijaya. Students were actively involved in material preparation, information delivery, and interactive discussions aimed at enhancing both conceptual understanding and practical skills. The presented material included definitions of labeling, its functions and benefits, as well as mandatory components such as product name, composition, net weight, expiration date, and distribution permit, in accordance with BPOM regulations and SNI standards. The results showed that students improved their understanding of proper food labeling and recognized its role as a communication tool between producers and consumers. Additionally, the activity positively impacted students’ readiness to face real-world business challenges, particularly in developing food products within small-scale industries or MSMEs. This program is expected to serve as a starting point for community empowerment through better understanding and innovation in food product labeling